2017
DOI: 10.1021/acsnano.7b00376
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling thein VivoProtein Corona of Circulating Leukocyte-like Carriers

Abstract: Understanding interactions occurring at the interface between nanoparticles and biological components is an urgent challenge in nanomedicine due to their effect on the biological fate of nanoparticles. After the systemic injection of nanoparticles, a protein corona constructed by blood components surrounds the carrier's surface and modulates its pharmacokinetics and biodistribution. Biomimicry-based approaches in nanotechnology attempt to imitate what happens in nature in order to transfer specific natural fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
100
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 50 publications
3
100
0
Order By: Relevance
“…cellular sequestration and subsequently experience acidification in the endolysosomal compartments in scavenger ECs. These biological processes we observed here mostly occurred within the first 1 h, and this underscores the importance of resolving early phase kinetics in the in vivo setting where rapid blood clearance is frequently reported also in mammalian models3,26,36 .…”
supporting
confidence: 69%
See 1 more Smart Citation
“…cellular sequestration and subsequently experience acidification in the endolysosomal compartments in scavenger ECs. These biological processes we observed here mostly occurred within the first 1 h, and this underscores the importance of resolving early phase kinetics in the in vivo setting where rapid blood clearance is frequently reported also in mammalian models3,26,36 .…”
supporting
confidence: 69%
“…Within 30 min following IV injections, FBS PC nanoparticles are rapid sequestered by scavenger ECs and acidified in the endolysosomal compartments(2). In a longer time-frame, degradation of the FBS PC occurs around 4-6 hpi in both scavenger ECs and macrophages while the former loses its integrity(3). Concurrently, macrophages are activated to an inflammatory phenotype (M1-like polarization) that secretes the cytokine Tnfa coordinating the onset of inflammation (4).…”
mentioning
confidence: 99%
“…opsonins) adsorbed in the PC are recognized by macrophages, are in the correct orientation and not masked with other proteins, they should be able to bind to macrophage receptors and be uptaken. 45 Just two hours after incubation we found that while NPs@PEG were not uptaken by the macrophages, NPs@Glc were highly uptaken. This confirms the results of the in vivo biodistribution, and has to be related with the different enrichment of proteins in each PC (as the amount of adsorbed proteins is similar), although their different orientation cannot be ruled out.…”
Section: Nps Biodistribution 72 H Post-injectionmentioning
confidence: 75%
“…This cross‐talk leads NPs to attach to specific receptors on the surface of phagocytes . Formation of protein corona has been shown to influence cell uptake, immune response, biodistribution, and fate of NPs . Protein corona could conceal the targeting moieties (such as peptides or antibodies), leading to impairment in NPs targeting capability …”
Section: Challenges and Limitations For In Vivo Delivery Of Npsmentioning
confidence: 99%